2018
DOI: 10.3892/ijmm.2018.3920
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin attenuates the inflammatory response via�inhibiting the C/EBP homologous protein-mediated pathway in taurocholate-induced acute pancreatitis

Abstract: Acute pancreatitis (AP) is a serious disease characterized by the activation of trypsin, autodigestion, edemas, hemorrhages and necrosis. However, the mechanisms of regulating the apoptosis and inflammation of acinar cells in AP remain unclear. The endoplasmic reticulum (ER) stress-related molecule, c/EBP homologous protein (cHOP), has pro-apoptotic and pro-inflammatory properties, in addition to regulating ER stress responses. In the present study, a lentivirus-mediated RNA interference (RNAi) approach was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…In the follow-up studies, the group also observed that melatonin not only suppresses the non-specific local but also the systemic inflammations induced by zymosan in rats (101,102). Thereafter, the anti-inflammatory activity of melatonin in different inducers, animal models and even in human clinical trials has been documented (103)(104)(105)(106). Inflammation is always manifested by neutrophil infiltration, increased microvascular leakage, tissue swelling and fever.…”
Section: Melatonin On Innate and Adaptive Immunitymentioning
confidence: 96%
“…In the follow-up studies, the group also observed that melatonin not only suppresses the non-specific local but also the systemic inflammations induced by zymosan in rats (101,102). Thereafter, the anti-inflammatory activity of melatonin in different inducers, animal models and even in human clinical trials has been documented (103)(104)(105)(106). Inflammation is always manifested by neutrophil infiltration, increased microvascular leakage, tissue swelling and fever.…”
Section: Melatonin On Innate and Adaptive Immunitymentioning
confidence: 96%
“…In a rat model for intracerebral hemorrhage, melatonin has been shown to exert neuroprotective effects via the suppression of the ATF6 pathway 233 . Melatonin was also shown to attenuate inflammation in LPS-induced AP in AR42J cells and in taurocholate-induced AP in rats 234,235 . Interestingly, pharmacologic ATF6 activation has also been shown to be protective in many diseases, including ischemic heart disease, and diabetes and neurodegenerative disorders [236][237][238][239][240] .…”
Section: Potential Treatment Of Alcoholic Pancreatitis By Targeting Er Stress and Uprmentioning
confidence: 92%
“…Through reporter-based assays, Bix, compound 147 (AA 147) and 263 (AA 263) have been identified and both specifically activate the ATF6 arm of the UPR [ 214 , 249 , 250 ]. Bix has been shown to exert beneficial effects in experimental models for multiple disease conditions, such as stroke and kidney injury [ 214 , 215 ]. In a mouse model of ischemic heart disease, AA 147 was shown to exert a protective effect in multiple tissues, including heart, brain, kidney and liver [ 216 ].…”
Section: Potential Treatment Of Alcoholic Pancreatitis By Targeting Er Stress and Uprmentioning
confidence: 99%